METHODOLOGICAL BASIS OF EFFECTIVE MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF TOURISM - TARASOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Global environmental issues such as climate change and criticism of the policies of multinational corporations make investing in environmentally conscious companies more relevant than ever. These issues pose a significant risk to investment portfolios, but the short-term goals of shareholders make these risks unattainable. In addition, corporate short-sightedness can cause a critical situation. Corporations need to consider other stakeholders when creating new products. This is due to the COVID-19 pandemic, which has shown that corporations need to consider other stakeholders and create green products. This is because they will help rebuild their current business model and deliver more value to shareholders, people and the planet in the long term. Many new green investment funds have been launched in the last five years. Some of these funds even outperformed traditional funds by some indicators.The purpose of the study is research, generalization and development of theoretical and methodological approaches regarding the features of sustainable investment in the development of ecologically oriented economy.The concept of sustainable development requires meeting the defined needs of society. This dictates two tasks: providing for the population with the lowest income level and reducing the limitations of the natural environment on the ability to meet social needs. One of the most important aspects of sustainable development is ecological balance, which promotes economic and ecological equality between people. In general, preserving the integrity of the ecosystem is important for ecologically sound development. Based on the results of the critical analysis, it was determined that Ukraine needs to take into account environmental sustainability, which is vital for its future existence. Mechanisms for investing in the development of an ecologically oriented economy through systemic modernization are proposed, mainly based on the transformation of the global financial system, the creation of new institutional structures, changes in the financial architecture, the formation of a global prudential regulatory framework, and the widespread introduction of green finance.The analysis of the latest world trends allows us to conclude that the greening of the economy has generally positive features. In addition, investment attractiveness in this sector is also growing due to, among other things, technological development, risk reduction and government support, which in difficult cases can attract additional capital investments, which, in turn, stimulates technological development. Therefore, the process is cyclical, which in turn contributes to the development of individual countries and socio-economic development as a whole.
Keywords: green economy; green financing; green projects; sustainable development; institutional investors